PTH-089 Hepatitis B Monotherapy With Tenofovir Or Entacavir: A Uk Single Centre Experience. (9th June 2014) - Shabbir, S; Stevenson, S; Tachtatzis, PM; Claridge, LC; Davies, MH; Jones, RL; Aldersley, MA
Abstract : Introduction: Tenofovir (TDF) and Entacavir (ETV) are potent oral antiviral medication for chronic hepatitis B 1 . Our aim was to record effectiveness of these 2 widely used antivirals in achieving viral suppression, HBeAg seroconversion and HBsAg loss after an initial 12 months of treatment and to further assess long term results (from June 2007 to April 2013) in chronic hepatitis B patients in a single tertiary referral centre. Methods: We retrospectively collected data from hospital record from June 2007 to April 2013. We included chronic hepatitis B patients with high viral load (>2000 IU/ml), treatment naive and treatment experienced and who were on treatment for at least 12 months with either on tenofovir or entacavir. Treatment experienced patients were those who were switched from other antivirals to tenofovir or entacavir with high viral load. Results: 61 patients were treated with TDF monotherapy for a median of 29 months, 25 (41%) were HBeAg positive and 36 (59%) were HBeAg negative. In the HBsAg positive group 17 (68%) achieved virological response in 12 months time while 22 (88%) had achieved it on longer term treatment. 2 (8%) got HBeAg seroconvertion within 12 months whilst 4 (16%) seroconverted on longer term treatment. In the HBeAg negative group 29 (81%) achieved virological response after 12 months treatment whilst 34 (94%) achieved virological response on longer term treatment. 33 patients were treated with ETV monotherapy for a median of 38 months, 14 (42%) were HBeAg positive and 19(58%) were HBeAg negative. In the HBsAg positive group 7 (50%) achieved virological response after 12 months treatment whilst all 14 (100%) achieved virological response on longer term treatment. 1 (7%) got HBeAg seroconvertion in 12 months whilst 4 (29%) seroconverted on longer term treatment. In the HBeAg negative group 15 (79%) achieved virological response after 12 months time whilst all 19 (100%) had achieved it on longer term treatment. None of the patients on either on ETV or TDF lost HBsAg. Conclusion: ETV and TDF are potent nucleos (t)ide analogues as first-line monotherapies for chronic hepatitis B. Due to the fact that ETV was licensed before TDF treatment durations are longer with this agent which is likely to explain the numerically superior long term results with ETV. It will require more patients and longer duration of treatment to allow a meaningful comparison of the two agents and to determine if HBsAg loss as described in the registration trials can be replicated in clinical practice. Reference: 1 Woo G, Tomlinson G, Nishikawa Y, et al . Tenofovir and entecavir are the most effective antiviral agents for chronic hepatitis B: a systematic review and Bayesian meta-analyses. Gastroenterology . 2010 Oct;139(4):1218-29 Disclosure of Interest: None Declared.